Implementasi proyek penguatan profil pelajar Pancasila dimensi berkebhinekaan global pada peserta didik kelas IV sekolah dasar - Oktavian Danar Al Farizi; St. Y Slamet; Sukarno Sukarno (Didaktika Dwija Indria, 2025)
This study aims to provide an overview of the analysis of the Pancasila  Student Profile on elements of global diversity conducted in the fourth grade of SD Negeri 3 Plumbon. The approach used in this research is qualitative. The data sources in this study come from students and teachers of the fourth grade at SD Negeri 3 Plumbon. The sampling technique used in this study is purposive sampling. The data collection techniques used are observation, interviews, and document studies. The results of this study first, indicate that the implementation,  consisting of the stages from planning to evaluation, has yielded positive results. Second, however, there are still obstacles, such as the lack of involvement of parents, the community, and the school in supporting the teaching and learning process; inadequate infrastructure, including the lack of learning equipment and culinary space; and low student independence. Third, the achievement results of the global diversity indicators can be described as follows: 83% of students on the cultural recognition indicator are developing as  expected. Additionally, 67% of students appreciate culture, and 75% show social justice, both in the expected development category.